Предмет: Алгебра,
автор: leshenkoevgeni
ПРИВЕДИТЕ К ВИДУ : ах2+вх +с = 0
1) (х-3)(3х+2)=(5х-4)(3х-2)
2)(2х+7)(7-2х)=49+х*(х+2)
Ответы
Автор ответа:
0
1) (х-3)(3х+2)=(5х-4)(3х-2)
3х^2+2x-9x-6=15x^2-10x-12x+8
3x^2-7x-6=15x^2-22x+8
3x^2-15x^2-7x+22x-6-8=0
-13x^2+15x-14=0
2) (2х+7)(7-2х)=49+х*(х+2)
14x-4x^2+49-14x=49+x^2+2x
-4x^2+49-49-x^2-2x=0
-5x^2-2x=0
3х^2+2x-9x-6=15x^2-10x-12x+8
3x^2-7x-6=15x^2-22x+8
3x^2-15x^2-7x+22x-6-8=0
-13x^2+15x-14=0
2) (2х+7)(7-2х)=49+х*(х+2)
14x-4x^2+49-14x=49+x^2+2x
-4x^2+49-49-x^2-2x=0
-5x^2-2x=0
Похожие вопросы
Предмет: Английский язык,
автор: NejasPLAY
Предмет: Другие предметы,
автор: adelinaazamatova57
Предмет: Физика,
автор: zhaniyabekbenbetova
Предмет: Физика,
автор: bradobrey